The Effect of Lactate, Albumin, C-reactive Protein, PaO2/FiO2 and Glucose Levels of Trauma Patients at the Time of Administration to Intensive Care - Eren Yılmaz; Canan Bor; Mehmet Uyar; Kubilay Demirağ; İlkin Çankayalı (Türk Yoğun Bakim Derneği Dergisi, 2014)
Objective: Blood analyses are preferred in the observation of cases requiring intensive care unit (ICU) following a trauma. The purpose of this study was to examine the relationship of albumin, C-reactive protein (CRP), PaO2/FiO2 and glucose levels of trauma patients at time of admission with mortality. Material and Method: The patients who were admitted into ICU following a trauma between the years of 2010 and 2012 were retrospectively evaluated. 200 trauma cases were included in the study. Their demographic data, APACHE II scores, Glasgow Coma Scales (GCS), and arterial blood gas in the lactate and PaO2/FiO2 ratio, CRP, glucose and albumin levels in the first collected arterial blood gas, as well as, the presence of thoracic, cardiac, renal, abdominal and head trauma, length of ICU stay and mortality were recorded. Results: Of the patients included in the study 84% were male, with an average age of 38.3 and an average APACHE II score of 16.6. 64% suffered from head trauma and the average GCS was calculated to be 11.2. The patients were observed in the ICU for an average of 18.7 days and the rate of mortality was 33.5%. GCS, PaO2/FiO2, age and elevated lactate levels increased mortality as independent risk factors. Conclusion: It has been concluded that parameters like age and the first GCS, lactate, glucose, albumin and PaO2/FiO2 at time of acceptance into the ICU were found to be related with mortality.